Development of plasmonic ELISA for the detection of anti-Leishmania sp. IgG antibodies - Santos Maciel, Marilene Oliveira dos [UNESP]; Soares, Matheus Fujimura [UNESP]; Costa, Sidnei Ferro [UNESP]; Bragato, Jaqueline Poleto [UNESP]; Freitas, Jessica Henrique de [UNESP]; Venturin, Gabriela Lovizutto [UNESP]; Melo, Larissa Martins [UNESP]; Rebech, Gabriela Torres [UNESP]; Reed, Steve; Felix de Lima, Valeria Marcal [UNESP] (Elsevier B.V., 2019)
Recently, a novel Enzyme-Linked Immunosorbent Assay (ELISA) strategy has emerged, known as plasmonic ELISA (pELISA), which enables the detection of disease biomarkers at low concentrations with the naked eye. For the first time, this research has developed a signal-generation mechanism for the detection of anti-Leishmania sp. IgG antibodies with the naked eye using pELISA. The immunoassay incorporates an indirect ELISA with successive growth of gold nanoparticles to obtain blue or red-colored solutions in the presence or absence of anti-Leishmania sp. IgG antibodies in canine serum, respectively. The technique we developed was successfully tested in canine serum positive and negative for canine leishmaniasis (CanL), and was shown to be an effective method that could be used as an additional tool for CanL diagnosis. It will be particularly useful in resource-constrained countries, because it does not require sophisticated instruments to read the results, increasing the practicality of CanL detection in these areas.
Keywords: Enzyme-linked immunosorbent assay; Metal nanoparticles; Canine Leishmaniasis